Impact of preoperative complement-dependent cytotoxicity crossmatch on postoperative outcomes in kidney transplant recipients: A retrospective analysis - Chonghe Xu; Siqi Xie; Meiyi Lu; Wei Xu; Mei Zhu (Journal of International Medical Research)
Objectives The aim of the present study was to compare the differences in clinical outcomes within 6 months postoperatively between a complement-dependent cytotoxicity <10% group of low-risk kidney transplant patients and a complement-dependent cytotoxicity ≥10% group of relatively high-risk patients. Methods The clinical data of 330 patients who underwent kidney transplantation were retrospectively analyzed. The patients were divided into three groups according to the results of complement-dependent cytotoxicity crossmatch: (a) group 1 (complement-dependent cytotoxicity ≥10%); (b) group 2a (5% ≤ complement-dependent cytotoxicity < 10%); and (c) group 2b (complement-dependent cytotoxicity <5%). The clinical outcomes were compared between the three groups. Results Significant differences were noted in serum creatinine levels and estimated glomerular filtration rate between groups 2a and 2b on days (D) 1, 2, 3, and 7 (P < 0.005). From postoperative D1 to month (M) 6, a significant difference (P < 0.05) was noted in urea levels between the three groups. On D3, blood glucose levels were significantly lower in group 2b than in group 2a (P < 0.001); at M6, group 2b exhibited lower blood glucose levels than group 1 (P = 0.043). On D2, group 2b had a lower neutrophil percentage than group 1 (P < 0.05), which was significantly different from those of groups 1 and 2a on D3 (P < 0.05). The percentage and absolute number of lymphocytes in group 2b were significantly higher than those in group 1 (P < 0.01) on D1 and D2. The percentage and absolute number of lymphocytes were significantly higher in group 2b than in groups 1 and 2a on D3 and D7 (P < 0.05). Conclusions Complement-dependent cytotoxicity <10%, particularly complement-dependent cytotoxicity <5%, was associated with superior attributes compared with complement-dependent cytotoxicity ≥10% in terms of most aspects of postoperative recovery and low incidence of adverse events. However, delayed graft function rate was highest in the complement-dependent cytotoxicity of 5%–10% group. The source of donor kidneys was the most important factor influencing delayed graft function, and a larger cohort with a longer follow-up period may be needed to verify the tendency.